Matematika darslarida ayrim interfaol metodlarning qo’llanilishi - Ismoilova Dildora Erkinovna (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
This article reflects the role and importance of interactive methods in the mathematics lesson, the use of some interactive methods in the lesson, their disadvantages and advantages are described.